The clinical application of non-genetic biomarkers for differential diagnosis of monogenic diabetes. - Owen, K; Skupien, J; Malecki, M (2009)
Diabetes mellitus is not a single disorder but rather a heterogeneous group of diseases that differ in respect to pathogenesis, the clinical picture and the response to dietary and pharmacological treatments. Thus, the differential diagnosis of various types and forms of diabetes is of great practical importance. This is particularly true for monogenic disease forms where some spectacular applications of pharmacogenetics have recently been described. Unfortunately, most patients with monogenic diabetes such as maturity-onset diabetes of the young (MODY) or neonatal diabetes have not undergone diagnostic molecular testing, so they can not benefit from the progress seen in this field. The reasons for this include the complexity and cost of molecular diagnostics. One of ways to change this situation is to find an efficient and cheap test to screen thousands of patients for specific forms of monogenic diabetes. These tests can be based on biomarkers discovered by one of two general strategies: a candidate approach or a systematic search based on metabonomics or proteonomics. This review summarizes recent advances in the search for putative biomarkers and the perspectives of the future progress.